China bound: A guide to academic life and work in the PRC - Anne F Thurston (National Academic, 1994)
The book introduces some of the available research and teaching opportunities and study programs. It explauns the structure of China's academic institutions and relates the experiences of other Americans who have work within them. It discusses the range of opportunities and suggests relevant strategies for archival and field research and collaborative projects in scientific laboratories. It provides advice ranging from preparation for departure to daily life in China